A porphyrin(2.1.2.1) bis-boron complex as a deep-red AIE luminophore induced by intermolecular F–π interaction. Issue 25 (10th June 2022) - Liu, Ningchao; Lv, Xiaojuan; Xiao, Bentian; Kuzuhara, Daiki; Mei, Peifeng; Aratani, Naoki; Yamada, Hiroko; Qiu, Fengxian; Pan, Jianming; Xue, Songlin
Abstract : Four novel boron complexes were synthesized from saddle-shaped porphyrins(2.1.2.1) as new cyclic ligands. The saddle shape confers unique structure-dependent photophysical properties, especially in emission. Abstract : Mono-/diboron complexes with saddle-shaped molecular conformations were synthesized from porphyrins(2.1.2.1). The boron complexes have unique structure-dependent photophysical properties: (a) monoboron complexes 2a and 2b are not emissive in solution and the solid state, (b) diboron complex 3a shows red emission in toluene, and (c) diboron complex 3b shows aggregation-induced emission (AIE) in the deep-red region due to intermolecular secondary interactions (F–π). This is the first case of a boron porphyrinoid complex that shows AIE emission in the deep-red region in decades.